Hubungan Disiplin Belajar dengan Motivasi Belajar Siswa pada Mata Pelajaran Fiqh Kelas IX MTs Al-Iqna Cisaga Kabupaten Ciamis - Rahmayani, Eva; Husni, Husni; Daryaman, Daryaman (Bestari, 2020)
This study aims to determine the relationship between learning discipline and student learning motivation in Fiqh subjects in class IX MTs Al-Iqna, Cisaga District, Ciamis Regency. This research method is quantitative research, in data collection techniques using a questionnaire for data collection. The results of the study, the students' learning discipline in class IX MTs Al-Iqna Cisaga was classified as moderate, because the average obtained was 65.83. This figure if classified into the research scale is classified as moderate, because it is in the range of r scores 62.22 - 69.42. And student learning motivation in the class IX fiqh subject is classified as moderate, because the average obtained is 64.37. This figure if classified into the research scale is classified as moderate, because it is in the range of scores of 61.78 - 66.92. Thus there is a relationship between learning discipline and student learning motivation in class IX Fiqh subjects, because based on the results of comparing t count with t table, the value of the Coefficient table (a) is obtained by the value of t count is 3,965, while t table is 2,048 When compared to t count> t table (3,965> 2,048), then Ho is rejected. Thus, it can be concluded that there is a significant influence between learning discipline on student learning motivation in class IX fiqh subjects. This is 36.0% change in learning motivation variable explained by changes in learning discipline variables. This means that there are still other factors as large as 64.0% that influence it.